2019
DOI: 10.17358/jma.16.2.170
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Farmer Entrepreneurial Competence on Broiler Farm Performance in Bogor

Abstract: The broiler is a highly demanded animal protein source for Indonesian people. Nowadays, primary and derived product demand for broiler chicken increases steadily. So it is necessary to increase broiler farm performance in order to meet the increased demand. One of the broiler farm centers which have fulfilled the rapid request of broiler chicken is located in Bogor, West Java. However, there was an important issue facing the broiler industry in Bogor, namely the decreased growth of broiler chicken population i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…Based on the hypothesis test result in Table 3, competency has significant effect to agripreneurship performance. This finding is in line with [26] . With a lot of farming experiences and training programs, the farmers already understand the cultivation procedures needed to maintain and increase land and crop productivity.…”
Section: Hypothesis Testingsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on the hypothesis test result in Table 3, competency has significant effect to agripreneurship performance. This finding is in line with [26] . With a lot of farming experiences and training programs, the farmers already understand the cultivation procedures needed to maintain and increase land and crop productivity.…”
Section: Hypothesis Testingsupporting
confidence: 90%
“…Entrepreneurial performance devided into production, income, market share and selling [11,19] . Several research findings stating that there is a relationship between competency and orientation toward performance [20][21][22][23][24][25][26][27] . Apart from having a direct effect on agripreneurship performance, competency also acts as a mediating variable to performance through entrepreneurial orientation [25] .…”
Section: Research Framework and Hypothesesmentioning
confidence: 99%
“…Entrepreneurial behavior has been found to have a beneficial relationship with business success in the ornamental plant business. Burhanuddin and Ramadhan (2019) found that entrepreneurial skill has a huge impact on the success of micro and small-scale enterprises. Entrepreneurial behavior and competence are expected to make ornamental plant entrepreneurs more proactive, imaginative, inventive, intelligent, and have a leadership spirit when it comes to running a company.…”
Section: Overview Of Ornamental Plant Business In the City Of Bogormentioning
confidence: 99%
“…In addition to the various competencies that scholars have identified, there are ongoing discussions about the key competencies that farmers primarily possess (Jama and Chellakan, 2020). According to Phelan and Sharpley (2012) and Burhanuddin and Ramadhan (2019), managerial competency is the most prevalent competency, whereas farmers lack core business competency. Nuthall (2006), on the other hand, asserted that risk management is an essential competency a farmer values most.…”
Section: Introductionmentioning
confidence: 99%